Potentiality of different seed priming agents to mitigate cold stress of winter rice seedling - Parvez Anwar, Md.; Ariful Islam Khalid, Md.; K. M. Mominul Islam, A.; Yeasmin, Sabina; Ahmed, Sharif; Hadifa, Adel; A. Ismail, Ismail; Hossain, Akbar; EL Sabagh, Ayman (Tech Science Press, 2021)
Seed priming has proved to be an effective pre-germination seed invigoration technique for different crops to improve seed and seedling performance under different abiotic stresses. In Bangladesh, winter rice is very often exposed to cold waves just after sowing in the nursery bed resulting in poor seed germination and seedling emergence, yellowish and thin seedlings production, and a very low survival rate. Seed priming may mitigate the cold stress during seed germination and seedling emergence and helps in the quality seedling production of winter rice. To evaluate the efficacy of different seed priming techniques in increasing seedling emergence, growth, vigor and survivability of winter rice cultivars under cold stress, a pot experiment was conducted at the Department of Agronomy, Bangladesh Agricultural University during December 2018 to January 2019. The experiment comprised two factors, (A) Winter rice variety namely, i) BRRI dhan29 and ii) BRRI dhan36; (B) Seed priming agent namely i) Control (no priming), ii) 20000 ppm NaCl, iii) 30000 ppm NaCl, iv) 20000 ppm KCl, v) 30000 ppm KCl, vi) 20000 ppm CaCl2, vii) 30000 ppm CaCl2, viii) 50 ppm CuSO4, ix) 75 ppm CuSO4, x) 10000 ppm ZnSO4, xi) 15000 ppm ZnSO4, xii) 2 ppm Na2MoO4, xiii) 3 ppm Na2MoO4, xiv) 100 ppm PEG (Polyethylene glycol 4000) and xv) 150 ppm PEG. Seeds were sown on two different dates viz., 1st December and 1st January so that seedlings are exposed to cold stress at different stages. The experiment was laid out in a completely randomized design (CRD) with three replications. Results indicated that (in most of the cases) seed priming has a positive impact on seedling emergence rate (%), root length, shoot length, root shoot ratio, root dry weight, shoot dry weight, seedling dry weight and survival rate (%). Among the priming agents, KCl and CaCl2 performed best; while priming with NaCl and PEG showed no advantages over no priming for both the sowing dates. In general, BRRI dhan36 performed better than BRRI dhan29 in terms of seedling growth because of its higher tolerance to cold stress. But, both the varieties performed similarly in terms of emergence rate and survival rate. Thus, priming is an effective tool to increase seed germination, better seedling growth, and higher seedling survivability of winter rice under cold stress, and KCl (20000 ppm) or CaCl2 (20000 ppm) can be considered as a viable priming agent.